PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA MANAJEMEN PADA DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN OGAN KOMERING ULU TIMUR - Susanti, Deviana; Wihana, Wihana; Malinda, Reka; Arafik, Arafik (Jurnal Signaling, 2024)
This research is a form of appreciation of organizational culture which can be believed in the success of employee in achieving success in each organization by development for the sake of smooth running of tasks in a compay or agency. Organizational culture is one way to build human resources for a company or agency throught several aspect of changing existing attitudes and behavior. This aims to make employess better and always be able to adapt early in facingperformanace challenges in the industrial era. Towords society, thi is where the function of human resource management is needed effectively and efficiently. Culture in the organization it self is a social force that is always invisible. However, in this case it turns out that it can mobilize the people within it to do the job as a whole. An employee oe employee in the organization will study adapt to the prevailing culture and be to judge what is goog and bad, right and wrong, permissible and not. Carried out in accordance with the regulations that have been made and agreed upon previously. Basically, the role of organizational culture triggers the beliefs and principle of an organization for the progress of the company or agency as a result of work done in team and working together.